Evaluation of the impact of Covid-19 on abnormal return of the socially responsible stocks and the most liquid stocks listed on IDX - Yulia Rahmadini; Aimatul Yumna (Universitas Negeri Padang, 2022)
The COVID-19 pandemic has impacted the investment climate in the Indonesian capital market, thus impacting investors' decisions in choosing resilient stocks during the pandemic. Socially responsible stocks are considred to be more reliable during crisis compared to other stocks. This study aims to determine the difference between abnormal returns before and after the announcement of COVID-19 as a global pandemic by the World Health Organization on March 11, 2020, against the SRI-Kehati and LQ45 indexes. Sample selection using purposive sampling technique with a sample of 17 companies SRI-Kehati and 21 companies LQ45. The data analysis used were one-sample t-test, one-sample Wilcoxon signed-rank test, Paired sample t-test, and Independent sample t-test. The results of this study indicate that there are significant abnormal returns and significant differences in average abnormal returns for the two indices. There is no significant difference in average abnormal return SRI-Kehati with average abnormal return LQ45. So, the results show that SRI-Kehati shares are more attractive to investors during the pandemic.